(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Safe drinking water is a cornerstone of public health protection. This study presents a comprehensive hygienic assessment of centralised drinking water supply quality, evaluating microbiological, physicochemical, and toxicological parameters in relation to population health outcomes. Findings highlight priority contaminants, quantified health risk levels, and actionable regulatory recommendations for improving water safety surveillance.